1995
DOI: 10.1046/j.1537-2995.1995.35996029155.x
|View full text |Cite
|
Sign up to set email alerts
|

Prestorage white cell reduction in saline‐adenine‐glucose‐mannitol red cells by use of an integral filter: evaluation of storage values and invivo recovery

Abstract: The combination of buffy coat removal and filtration in the blood container system with an integral filter achieved effective WBC reduction (> or = 3 log10 reduction from whole blood) without biologically significant detriment to in vitro or in vivo storage values.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
14
0
1

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 27 publications
5
14
0
1
Order By: Relevance
“…5 leucodepletion and is comparable with data published for other third-generation filtration systems (Heaton et al, 1994;Riggert et al, 1995;Rogers et al, 1995). Indeed, our work supports previous studies which showed significantly less haemolysis and potassium leakage in leucodepleted units (Heaton et al, 1994;Rogers et al, 1995). This may be attributed to several factors including temperature/time induced alterations in the adhesive capacity and deformability of blood cells as well as leucocyte fragmentation (Steneker et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…5 leucodepletion and is comparable with data published for other third-generation filtration systems (Heaton et al, 1994;Riggert et al, 1995;Rogers et al, 1995). Indeed, our work supports previous studies which showed significantly less haemolysis and potassium leakage in leucodepleted units (Heaton et al, 1994;Rogers et al, 1995). This may be attributed to several factors including temperature/time induced alterations in the adhesive capacity and deformability of blood cells as well as leucocyte fragmentation (Steneker et al, 1995).…”
Section: Discussionsupporting
confidence: 91%
“…Previous studies (Rogers et al, 1995) provide equivalent data for buffy coat depleted (1 log) products prepared in the Optipac 1 configuration. Component separation was performed on Optipress 1 automated blood component extractors (Baxter) according to the manufacturer's instructions.…”
mentioning
confidence: 99%
“…Even though hemolysis rates increased over the 42‐day period, they were still well below the limit of 0.8 percent that was suggested by the international standards 17 . After 42 days, analysis of the remaining storage variables, such as pH, supernatant potassium, ATP/Hb, and 2,3 DPG, revealed results similar to previously published data 12 and our own observations in buffy coat‐depleted RBCs 10 . Thus, we found no detrimental effects of prestorage WBC filtration on RBC storage.…”
Section: Discussionsupporting
confidence: 90%
“…It has also been described by various authors that the presence of leukocytes in the red cell units contribute significantly to an increase in red cell hemolysis during storage,[71011] and that prestorage filtration helps in reducing the extent of this hemolysis. [1314] This is due to the release of various chemicals and enzymes, especially proteases from the leukocytes. For the same reason, various leukocytes reduction filters are commercially available.…”
Section: Discussionmentioning
confidence: 99%